Amelioration in Indonesian Classics: A Corpus Analysis of Concrete Nouns in Indonesian Literary Works - Lubis, Nurhabibah; Ermanto, Ermanto (Universitas Pendidikan Mandalika, 2025)
This research analyzes the phenomenon of amelioration on concrete nouns in the novels Layar Terkembang by Sutan Takdir Alisjahbana and Sitti Nurbaya by Marah Roesli. Amelioration is the process of changing the meaning of a word that leads to a more positive connotation. The purpose of this study is to identify the forms of amelioration, the positive connotations formed, and how these changes in meaning reflect the social and cultural context of colonial Indonesia. The research method used is corpus linguistics with documentation techniques through the KORTARA (Korpus Nusantara) application to identify frequency patterns and word collocation in literary texts. The results showed that there were 57 words undergoing amelioration that reflected changes in social views, culture, and religious values. For example, the word